2014
DOI: 10.4172/2327-4972.1000115
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Utilization of Post Abortion Care in Selected Governmental Health Institutions, Addis Ababa, Ethiopia

Abstract: IntroductionWorldwide, each year more than 500,000 women, 99% of them in developing countries, die from pregnancy and childbirth-related complications and an additional 15 to 20 million women suffer from debilitating consequences of pregnancy [1]. The major causes of maternal deaths are hemorrhage, infection, obstructed labor, hypertensive disorders in pregnancy, and complications of unsafe abortion [2].Maternal deaths due to unsafe abortion in developing countries fall within a narrow range from 9% to 17% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
1
3
1
Order By: Relevance
“…Women whose monthly income was 5000 ETB and above were less likely to use PAFP than those women whose monthly income was less than 5000 ETB. This is contrary to another Ethiopian study from Addis Ababa, which found no significant association between use of post-abortion contraception and monthly income of the client [23].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Women whose monthly income was 5000 ETB and above were less likely to use PAFP than those women whose monthly income was less than 5000 ETB. This is contrary to another Ethiopian study from Addis Ababa, which found no significant association between use of post-abortion contraception and monthly income of the client [23].…”
Section: Discussioncontrasting
confidence: 99%
“…Several factors are associated with women's decisions regarding starting post-abortion family planning. Studies done in Ethiopia indicate that urban residence, higher maternal education level, occupation, undergoing spontaneous abortion, receiving post abortion family planning counseling, good knowledge of family planning, and availability of family planning are significantly associated with uptake of family planning in the postabortion period [16,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete abortion occurring in gestational age beyond 12 weeks had 3.4 times more risk developing unfavorable management outcome. This finding is in line with several studies' findings conducted in Ethiopia [ 9 , 10 , 14 ]. This is because as the fetus in the uterus grows older, the size of conceptus and blood supply is increased very much which in turn results in extensive bleeding and uterine manipulation, which harms the mother and make outcome of abortion management unfavorable.…”
Section: Discussionsupporting
confidence: 93%
“…The sample size for the second objective is calculated by taking estimated proportions of the most common risk factors determining management outcome of incomplete abortion (duration of vaginal bleeding <3 days = 80% and OR = 7.5) according to a study conducted in Adigrat Zonal Hospital, Tigray Region, Northern Ethiopia [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…A key strength of this study is that both survey-administered interviews and IDIs were conducted in communities, and the research staff and individual respondents determined the place of interview together. This is in contrast to most post-abortion studies in which data collection occurs in health facilities [ 3 , 26 29 ] and carries a high risk of bias introduced by the health facility environment. Another strength of this study is the concurrent qualitative and quantitative methods, which ensured both breadth and depth and which is rarely the case in abortion research, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 92%